the HEALTH EDUCATION RELATED TO “NUTRITION AND MENTAL HEALTH” - Mawarni, Elita Endah; ALFIAN, ALFIAN ABDUL RAJAB, S.Tr.Gz., M.Gz.; Mulya, MULYA AGUSTINA, S.Gz., M.Si.; Agus, AGUS PUTRA MURDANI, S.KM, M.Kes (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2025)
In our daily lives, nutrition and mental health are two inseparable aspects. Both are the most important parts in maintaining our physical and mental health. This community service activity aims to increase knowledge and understanding and the role of adolescents in maintaining mental health by linking it to balanced nutritional consumption. It is hoped that by knowing the importance of maintaining mental health by fulfilling balanced nutrition, it can reduce the incidence of mental health crises in adolescents. Nutrition is one of the important factors that determines the level of health and in schools. The method used is an interactive lecture and Q&A to students of SMP N 3 Purwoharjo Satu Atap regarding the prevention of mental health crises through the fulfillment of balanced nutrition in adolescents using observation techniques and pre-test data collection with the aim of determining whether or not this educational activity is necessary. Pre-test and post-test analysis are used to determine whether or not there is a change in understanding about prevention and how to prevent mental health crises through the fulfillment of balanced nutrition. The results of educational activities have an effect on increasing the understanding of students of SMP N 3 Purwoharjo Satu Atap about how to prevent mental health crises through the fulfillment of balanced nutrition. Keywords: Mental health, adolescents, balanced nutrition